1988
DOI: 10.1007/bf00014950
|View full text |Cite
|
Sign up to set email alerts
|

Transcription study of the genes encoded in the region of the junction between the large single copy and the inverted repeat A of spinach chloroplast DNA

Abstract: The expression of the psbA, trnH-GUG and rps19' genes from spinach chloroplasts, coding respectively for the 32 kDa protein, the tRNA(His) (GUG), and the putative ribosomal protein CS19', has been studied by cloning, Northern hybridization and 3' and 5' S1 mapping experiments.It is demonstrated that the putative transcription termination signal of the psbA gene does not function as a rho-independent terminator of transcription in E. coli, whatever its orientation.Evidence is presented suggesting that, in spina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Nuclear and mitochondrial probes were from maize. The following DNA fragments were used as probes: the 750 bp XbaI-PstI intragenic fragment of the psbA gene (26); the 550 bp SaIl-EcoRV fragment containing the rpsl9 gene (27); the 1200 bp EcoRI-PstI intragenic fragment of the rbcL gene (30); the 1200 bp EcoRI-BamHI intragenic fragment of the rrn 16S gene (1); the 1200 bp EcoRI-HindIII intragenic fragment of the atp6 gene (8); the 2200 bp XbaI fragment containing the atp9 gene (9); the intragenic 680 bp HindIII-EcoRI fragment of the cob gene(6); the 1000 bp EcoRI intragenic fragment ofthe rbcS gene. Labeling ofinserts was done by the random hexamer priming method to a specific activity ranging from 1 to 5 x 109 cpm/,ug.…”
Section: Chloroplast Dna Preparationmentioning
confidence: 99%
“…Nuclear and mitochondrial probes were from maize. The following DNA fragments were used as probes: the 750 bp XbaI-PstI intragenic fragment of the psbA gene (26); the 550 bp SaIl-EcoRV fragment containing the rpsl9 gene (27); the 1200 bp EcoRI-PstI intragenic fragment of the rbcL gene (30); the 1200 bp EcoRI-BamHI intragenic fragment of the rrn 16S gene (1); the 1200 bp EcoRI-HindIII intragenic fragment of the atp6 gene (8); the 2200 bp XbaI fragment containing the atp9 gene (9); the intragenic 680 bp HindIII-EcoRI fragment of the cob gene(6); the 1000 bp EcoRI intragenic fragment ofthe rbcS gene. Labeling ofinserts was done by the random hexamer priming method to a specific activity ranging from 1 to 5 x 109 cpm/,ug.…”
Section: Chloroplast Dna Preparationmentioning
confidence: 99%
“…Zurawski et al (746) found that the first 48 codons of rpsl9 in spinach were in the inverted repeat, with 44 codons homologous to the 3' end of the E. coli gene being present only on one side of the large single-copy region. Thomas et al (635,636) showed that this complete copy of the gene was expressed, whereas the rpsl9' sequences beginning in the other side of the inverted repeat and extending for 66 codons into the adjoining unique sequence region (745) were not transcribed. The rpsl9 gene also straddles the boundary of the inverted repeat in Spirodela oligorhiza (494) and in mustard (454).…”
Section: Proteins Of the Small Subunitmentioning
confidence: 99%
“…Based on its length and the fact that it did not hybridize to probe KH ( Figure 3), it appears that the 1.7 kb RNA covers both of the psbA and trnH genes. A corresponding, bicistronic transcript has not readily been detected in other species, although the psbA and trnH genes have been previously assumed to be co-transcribed (Gruissem and Zurawski, 1985;Thomas et a/., 1988).…”
Section: Pinus Sylvestrismentioning
confidence: 99%